2005
DOI: 10.1080/13607860500090052
|View full text |Cite
|
Sign up to set email alerts
|

The CORE-OM in an older adult population: Psychometric status, acceptability, and feasibility

Abstract: There is a need to extend and test the feasibility and acceptability of mental health outcome measures in the older population (i.e., aged 65-100). We present data on the CORE-OM (Clinical Outcomes in Routine Evaluation-Outcome Measure) on a sample of 118 people aged 65-97 presenting for mental health treatment and 214 people aged 65-94 drawn from a non-clinical population. Results show the CORE-OM to be a reliable measure in both samples when the overall mean item is used but the reliability is not as high fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 13 publications
2
30
3
2
Order By: Relevance
“…While the cross-sectional nature of this research prohibits a definitive statement about change over time in these specific women, their results do differ from the findings of Foa and colleagues (1997) in norming the instrument with a considerably younger population. This is consistent with the results of Barkham et al (2005), who recommended that different norms and cut-off scores be established for a mental health measure, based on respondents' 386 C. L. Bright and S. E. Bowland ages. These results can be interpreted in more than one way.…”
Section: Summary Of Pds Findingssupporting
confidence: 89%
“…While the cross-sectional nature of this research prohibits a definitive statement about change over time in these specific women, their results do differ from the findings of Foa and colleagues (1997) in norming the instrument with a considerably younger population. This is consistent with the results of Barkham et al (2005), who recommended that different norms and cut-off scores be established for a mental health measure, based on respondents' 386 C. L. Bright and S. E. Bowland ages. These results can be interpreted in more than one way.…”
Section: Summary Of Pds Findingssupporting
confidence: 89%
“…The CORE-Outcome Measure (CORE-OM; Barkham et al, 2001) has been used extensively in primary care services in the UK for over a decade to provide measures of psychological functioning (Barkham, Culverwell, Spindler, & Twigg, 2005;Evans et al, 2000). The shortened 10-item version (CORE-10; Barkham et al, 2013) has also been validated against CORE-OM, has been shown to be sensitive to change, and provides a measure of general psychological functioning.…”
Section: Clinical Outcomes In Routine Evaluationmentioning
confidence: 99%
“…Model IV was the three factor model specified by Barkham et al [29] for their clinical population (which they consider to be of principal interest) with items 1, 2, 5, 11, 13, 14, 15, 17, 20, 23, and 27 loading onto factor one: ‘negatively worded', items 3, 4, 7, 12, 19, 21, 31 and 32 loading onto factor 2, ‘positively worded’, and items 6, 9, 16, 22, 24, 25, 26, 29, 33, and 34 loading onto factor 3, ‘risk’.…”
Section: Methodsmentioning
confidence: 99%
“…Factor loadings were moderate to high, but item 8 (“I have been troubled by aches, pains or other physical problems”) was rejected for the student group because it did not load onto any factor. Barkham et al [29] also reported a three factor solution to their data from two samples of older adults (aged 65–97); of which 118 were adults attending mental health services, and 214 were adults from the general population. However, the items were differently distributed across the factors compared with Evans et al [24] and five items were excluded as they had low factor loadings <0.4.…”
Section: Introductionmentioning
confidence: 99%